2015
DOI: 10.1242/jeb.121384
|View full text |Cite
|
Sign up to set email alerts
|

Snake constriction rapidly induces circulatory arrest in rats

Abstract: As legless predators, snakes are unique in their ability to immobilize and kill their prey through the process of constriction, and yet how this pressure incapacitates and ultimately kills the prey remains unknown. In this study, we examined the cardiovascular function of anesthetized rats before, during and after being constricted by boas (Boa constrictor) to examine the effect of constriction on the prey's circulatory function. The results demonstrate that within 6 s of being constricted, peripheral arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
0
34
1
Order By: Relevance
“…Later, Moon and Mehta (2007) tested snakes of different species and sizes, and inferred that low pressures may cause suffocation, moderate pressures may cause circulatory arrest, and extremely high pressures may cause spinal injury. Boback et al (2015) nicely extended this earlier work by directly measuring circulatory function in rats during constriction; they showed that a constriction pressure of 20 kPa can severely impede cardiac and circulatory function in rats. In the prey, heart rate decreased, cardiac electrical activity became abnormal, and blood pressure increased ca.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Later, Moon and Mehta (2007) tested snakes of different species and sizes, and inferred that low pressures may cause suffocation, moderate pressures may cause circulatory arrest, and extremely high pressures may cause spinal injury. Boback et al (2015) nicely extended this earlier work by directly measuring circulatory function in rats during constriction; they showed that a constriction pressure of 20 kPa can severely impede cardiac and circulatory function in rats. In the prey, heart rate decreased, cardiac electrical activity became abnormal, and blood pressure increased ca.…”
Section: Introductionmentioning
confidence: 57%
“…When fighter pilots experience negative gravitational accelerations (G-forces), they incur a rush of blood to the brain that causes rapid loss of consciousness (Balldin, 2002). Constriction pressures above the venous blood pressure of the prey will impede blood flow and oxygen delivery to tissues (reviewed by Moon and Mehta, 2007;Boback et al, 2015). Constriction pressures dramatically higher than the prey's blood pressure could force blood away from the site of constriction and into the extremities, including the head and brain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both morphology and physiology are important, behavior can determine the ways in which morphological elements and physiological capacities are used (Hertz et al, 1982). For snakes that use constriction behavior, predation performance can be evaluated by measuring peak constriction pressure (Moon, 2000;Moon and Mehta, 2007;Boback et al, 2015;Penning et al, 2015;Penning and Dartez, 2016). Constriction pressure is a biologically important measure of performance (Moon and Mehta, 2007) because it can determine the time needed to subdue the prey and reduces the chances of prey escaping or causing injury to the snake.…”
Section: Introductionmentioning
confidence: 99%